Different Neurogenic Potential in the Subnuclei of the Postnatal Rat Cochlear Nucleus - Johannes Voelker; Jonas Engert; Christine Voelker; Linda Bieniussa; Philipp Schendzielorz; Rudolf Hagen; Kristen Rak (Hindawi Limited, 2021)
In patients suffering from hearing loss, the reduced or absent neural input induces morphological changes in the cochlear nucleus (CN). Neural stem cells have recently been identified in this first auditory relay. Afferent nerve signals and their impact on the immanent neural stem and progenitor cells already impinge upon the survival of early postnatal cells within the CN. This auditory brainstem nucleus consists of three different subnuclei: the anteroventral cochlear nucleus (AVCN), the posteroventral cochlear nucleus (PVCN), and the dorsal cochlear nucleus (DCN). Since these subdivisions differ ontogenetically and physiologically, the question arose whether regional differences exist in the neurogenic niche. CN from postnatal day nine Sprague-Dawley rats were microscopically dissected into their subnuclei and cultivated in vitro as free-floating cell cultures and as whole-mount organ cultures. In addition to cell quantifications, immunocytological and immunohistological studies of the propagated cells and organ preparations were performed. The PVCN part showed the highest mitotic potential, while the AVCN and DCN had comparable activity. Specific stem cell markers and the ability to differentiate into cells of the neural lineage were detected in all three compartments. The present study shows that in all subnuclei of rat CN, there is a postnatal neural stem cell niche, which, however, differs significantly in its potential. The results can be explained by the origin from different regions in the rhombic lip, the species, and the various analysis techniques applied. In conclusion, the presented results provide further insight into the neurogenic potential of the CN, which may prove beneficial for the development of new regenerative strategies for hearing loss.